Dry powder and short fuses: Private equity funds in emerging markets - Fang, Dawei (Journal of Corporate Finance, 2019)
One puzzling feature of domestic private equity (PE) funds in emerging markets is that such funds often have a “short fuse”, i.e., a much shorter lifespan than their developed market counterparts. Based on a simple agency model, we propose an explanation for this puzzle. We show that, under a long fuse, PE managers have incentives to game performance-based compensation schemes by opportunistically timing investments and burning money when early investments fail. Shortening the fuse restricts timing opportunism, but alleviates money-burning incentives only if managerial compensation is sufficiently concavified or the contract stipulates substantial investors' hurdle returns. Both of these options can force managers to concede rents to investors. Thus, managers face a tradeoff between rents and agency costs. In emerging markets, where agency costs are high, managers use a short fuse with incentive compatible compensation schemes to minimize agency costs. In contrast, in developed markets, where agency costs are low, managers use a long fuse to preserve rents. Based on these results, we further draw predictions on fund performance, managerial behavior, and investor rents for both long-fused developed-market funds and short-fused emerging-market funds. We also predict that, when institutional infrastructure in emerging markets improves and when domestic PE managers in emerging markets gain more experience, domestic PE funds in emerging markets will adopt the long-lifespan PE contracts typical in developed markets.